Effect of Hypervitaminosis a on the Histological Structure of Heart in Male Albino Rat - Al-awsi, Nawraa abd Al-sattar; Bargooth, Ali Fayadh (American Journal of Biology and Natural Sciences, 2025)
Vitamin A (VA) is a fat-soluble compound. There are two types of VA, the first type is retinol and retinoic acid (derived from animal sources) and the second type is carotenoid derived from plant sources (1,2). In 1928, Green and Milandi reported that vitamin A could enhance the anti-inflammatory response of organisms and called vitamin A the “anti-inflammatory vitamin” (3). VA is naturally present in many foods. VA is important for normal vision, the immune system, reproduction, growth, and development. VA also helps the heart, lungs, and other organs function properly. Carotenoids are pigments that give yellow, orange, and red fruits and vegetables their color. The human body is able to convert some carotenoids to VA (4). VA has also been reported to influence the composition and diversity of gut microbes (5).